Régimen jurídico de la energía eléctrica en Ecuador: tensiones socioambientales y con los derechos de la naturaleza (Tema Central) - Martínez Moscoso, Andrés (2024)
Socio-environmental conflicts are part of the national reality, one of them is the sovereignty of the natural resources in contrast with the Nature rights. Therefore, it’s important to understand energy sovereignty from the role of the governments in power, which took advantage of the national geography for the development and generation of renewable energies. However, political-clientelated interest, as well as regulatory modifications, hindered its achievement for a long time. This paper studies the legal regime of the electric energy, starting from its historical evolution, in the different models of public and private management. The methodology used is an historical legal review, which identified the different regulations and actions of the State in the administration, management, and control of the electricity sector. It was noted that, the Special Rapporteur on the human right to water and sanitation recommends that, for the development of large infrastructures, natural resources should be governed efficiently through the trinomial, water, energy, and food, strategy which allows fewer conflicts. For this reason, the cases of study were considered are the Dulcepamba River and the Machángara River basin, with the purpose of showing the negative and positive experiences in terms of governance.socio-environmental